2002
DOI: 10.1274/jmor.19.81
|View full text |Cite
|
Sign up to set email alerts
|

Both Ca2+-Protein Kinase C Pathway and cAMP-Protein Kinase A Pathway are Involved in Progesterone Production in FSH- and LH-stimulated Cumulus Cells during In Vitro Maturation of Porcine Oocytes

Abstract: Abstract:We investigated the role of cAMP-Protein kinase A pathway and Ca 2+ -Protein kinase C pathway w hich were activated by FSH and/or LH in the progesterone production by cumulus cells during in vitro m a t u r a t i o n o f p o r c i n e o o c y t e s . T h e l e v e l o f progesterone in the medium in which COCs had been cultured for 24 hr without FSH was 7.8 ± 1.5 ng/ml. The addition of FSH significantly increased the progesterone level in a dose-dependent fashion during 24-hr cultivation of COCs; a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We have already shown that progesterone production in cumulus cells is significantly increased after 10 h of cultivation (Shimada et al 2002). In Fig.…”
Section: The Roles Of Pr-a and Pr-b In Proliferation Of Cumulus Cellsmentioning
confidence: 53%
“…We have already shown that progesterone production in cumulus cells is significantly increased after 10 h of cultivation (Shimada et al 2002). In Fig.…”
Section: The Roles Of Pr-a and Pr-b In Proliferation Of Cumulus Cellsmentioning
confidence: 53%
“…1980; Richards 1994). In porcine COC, we reported that the addition of LH to the FSH‐containing medium also produced a significant increase of progesterone production (Shimada et al . 2002a).…”
Section: Resultsmentioning
confidence: 99%